Industrial training report: Creative Media and Technology (CMTHub) / Mohamad Zharif Farid Rizal - Farid Rizal, Mohamad Zharif (Universiti Teknologi MARA, Negeri Sembilan, 2024)
This report describes the experiences and lessons learned during an eight-week industry training program at the Creative Media and Technology Hub (CMTHub), Universiti Teknologi MARA, Shah Alam. The curriculum attempted to connect theoretical knowledge to practical applications, with a focus on digital media production, event management, and multimedia content development. The primary responsibilities included generating promotional materials, photographing events, conducting interviews, and using DSLR cameras. The internship helped me improve my technical skills, leadership, cooperation, and problem-solving talents while also encouraging creativity and adaptation in a fast-paced workplace. The report emphasizes the importance of industry training in providing students with real world skills and insights, outlines CMTHub's organizational structure and functions, and describes training programs. It finishes with thoughts on personal development, learning results, and suggestions for strengthening CMTHub's operations and internship program. The experience gave the intern excellent professional experience and equipped her for future opportunities in multimedia creation and information management.